Wingless capture by Frizzled and Frizzled2 in Drosophila embryos. - Lecourtois, M.; Alexandre, C.; Dubois, L.; Vincent, J.P. (Developmental Biology, 2001)
A variety of factors could influence how far developmental signals spread. For example, the Patched receptor limits the range of its ligand Hedgehog. Somehow, the Frizzled2 receptor has the opposite effect on its ligand. Increasing the level of Frizzled2 stabilizes Wingless and thus extends the Wingless gradient in Drosophila wing imaginal disks. Here we ask whether Frizzled or Frizzled2 affects the spread of Wingless in Drosophila embryos. We show that in the embryonic epidermis, the combined expression of both receptors is lowest in the engrailed domain. This is because expression of Frizzled is repressed by the Engrailed transcription factor, whereas that of Frizzled2 is repressed by Wingless signaling. Receptor downregulation correlates with an early asymmetry in Wingless distribution, characterized by the loss of Wingless staining in the engrailed domain. Raising the expression of either Frizzled or Frizzled2 in this domain prevents the early disappearance of Wingless-containing vesicles. Apparently, Wingless is captured, stabilized, and quickly internalized by either receptor. As far as we can tell, captured Wingless is not passed on to further cells and does not contribute to the spread of Wingless. Receptor downregulation in the posterior compartment may contribute to dampening the signal at the time when cuticular fates are specified.